Qualitative Investigation (Conceptual Synthesis) - Martínez M., Miguel (2006)
The Document offers an ample panorama us of the qualitative investigation. It initiates with necessary revision of the subject of the knowledge, boarded from his epistemologic nature to be able to understand the concrete totality of the reality, and in the terminology of the author, like an all polisistémico and interdisciplinariedad. In background it identifies the dynamic dimension of the qualitative investigation, as soon as it tries to identify the deep nature of the realities, his structure and relations that settle down, to fulfill the two tasks basic of all investigation: To gather data and to categorizar them and to interpret them. It makes a treatment of the referential frame, the objectives, the hypotheses and the variables, identifying several qualitative methods, as well as the instruments and procedures.